The Laparoscopic Anatomy of Rouviere’s Sulcus - Abdelfattah MR (Dove Medical Press, 2021)
Mohamed Rabei Abdelfattah Department of Surgery, University of Alexandria, Faculty of Medicine, Alexandria, EgyptCorrespondence: Mohamed Rabei AbdelfattahDepartment of Surgery, Faculty of Medicine, AL Khartoum Square, PO Box 21131, Azzaritta, Alexandria, EgyptEmail Mohamad.rabie@gmail.comBackground: Laparoscopic cholecystectomy (LC) is incapacitated by occurrence of bile duct injury (BDI). Precise identification of the frequently variable biliary anatomy is important for prevention of BDI. Rouviere’s sulcus received a significant interest as useful landmark to prevent BDI. This study aims to describe the frequency of Rouviere’s sulcus, its various patterns, dimension and to assess its usefulness as a landmark during LC.Methods: The study was carried on 100 consecutive cases of LC performed at our center between July 2017 and July 2018. Analysis of video recording of the laparoscopic procedure together with operative measurements was used to assess frequency, pattern, direction and various measurements of Rouviere’s sulcus.Results: Rouviere’s sulcus was evident during LC in 86% of cases and the sulcus type (whether open or closed) constituted 80.2% of evident Rouviere’s sulcus. The average measurement for this type was found to be about an inch in length, and less than 1 cm in both width and depth. Closed type of Rouviere’s sulcus was significantly narrower compared to open type (p = 0.00), while the difference in length and depth did not reach statistical significance.Conclusion: Rouviere’s sulcus is evident in majority of cases with sulcus type as its commonest pattern. Rouviere’s sulcus served as a useful landmark if it was visualized and not vertically directed. It allows for safe biliary dissection through identifying the level of common bile duct in more 86% of cases.Keywords: Rouviere’s sulcus, laparoscopic cholecystectomy, bile duct injury, LC, BDI